Examining air pollution dynamics in Ploiesti: a focus on vehicular emissions - Georgeta-Olguta Gavrila; Oana Cristina Parvulescu; Cristian Constantin; Valeriu Danciulescu; Simona Mariana Calinescu; Gheorghita Tanase; Valentin Stancu (Romanian Journal of Ecology & Environmental Chemistry)
This paper presented the topic of urban air pollution in Ploiesti Municipality, located 60 km north of Bucharest. The study analyses the seasonal variations in 2023 of air pollutants such as nitrogen dioxide (NO2), sulphur dioxide (SO2) and particulate matter (PM10), the impact of road traffic on air quality, as well as the monitoring measures according to the in force environmental legislation. For the air quality assessment two types of data were collected: data from the National Air Quality Monitoring Station (AQMS) of Ploiesti for the winter ÷ summer period and data obtained from field measurements carried out in November. The location of the sampling points took into account several factors such as: pollution source (road traffic, industry), measured meteorological parameters (temperature, humidity, atmospheric pressure, wind speed and direction). The experimental data were analysed using Principal Component Analysis (PCA), and were also compared with AQMS values. The comparisons between measured and AQMS data showed significantly higher concentrations for the samples (P1, P2, P3), which could indicate the presence of local sources of SO2 emissions or conditions favouring the accumulation of this pollutant. The PCA indicate that the higher concentrations of pollutants seemed to be associated with cooler temperatures and reduced solar radiation, suggesting a significant impact of meteorological conditions on the distribution of pollutants.